2008
DOI: 10.1128/jb.00414-08
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensitivity and Cell Division Defects in an Escherichia coli Strain with Mutations in yghB and yqjA , Encoding Related and Conserved Inner Membrane Proteins

Abstract: Ludox density gradients were used to enrich for Escherichia coli mutants with conditional growth defects and alterations in membrane composition. A temperature-sensitive mutant named Lud135 was isolated with mutations in two related, nonessential genes: yghB and yqjA. yghB harbors a single missense mutation (G203D) and yqjA contains a nonsense mutation (W92TGA) in Lud135. Both mutations are required for the temperature-sensitive phenotype: targeted deletion of both genes in a wild-type background results in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
99
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 46 publications
(48 reference statements)
4
99
0
Order By: Relevance
“…The membrane and cell division defects of BC202 are present at both the permissive and nonpermissive growth temperatures. However, BC202 is not hypersensitive to antibiotics or detergents, likely signifying an intact outer membrane, under permissive growth conditions (35). We have demonstrated that the periplasmic amidases AmiA and AmiC are not exported to the periplasm in E. coli mutant BC202 (31).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The membrane and cell division defects of BC202 are present at both the permissive and nonpermissive growth temperatures. However, BC202 is not hypersensitive to antibiotics or detergents, likely signifying an intact outer membrane, under permissive growth conditions (35). We have demonstrated that the periplasmic amidases AmiA and AmiC are not exported to the periplasm in E. coli mutant BC202 (31).…”
mentioning
confidence: 84%
“…Each of the dedA homologs in E. coli (yqjA, yghB, yabI, yohD, dedA, ydjX, ydjZ, and yqaA) is individually nonessential as the single gene knockouts have been made and are available in the Keio collection (1). Our group has determined that simultaneous deletion of yghB and yqjA from E. coli results in a strain (named BC202; ⌬yghB::Kan r ⌬yqjA::Tet r ) that has abnormal membrane phospholipid composition, does not complete cell division (forming chains of cells), and fails to grow at 42°C (35). YghB and YqjA are proteins of 219 and 220 amino acids, respectively, displaying 61% amino acid identity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, while the lipid composition of the membrane is crucial for its function, integral membrane proteins may also play a significant role, particularly with respect to the temperature limit of an organism's growth range. For example, mutations of integral membrane proteins of the DedA family cause temperature sensitivity and cell division defects in Escherichia coli (Thompkins et al 2008). Interestingly, proteins from the DedA family have been shown to be essential in at least 2 bacterial species (E. coli and Borrelia burgdorferi), but their homologs are not detected in several thermophilic and hyperthermophilic Thermotogae genomes (Doerrler et al 2013).…”
Section: Thermosipho Japonicus (Ab024932)mentioning
confidence: 99%
“…Interestingly, in Bacillus a transmembrane 2-component response regulator, which controls the desaturase that introduces double bonds in preexisting fatty acids, senses changes in membrane fluidity and not the actual temperature changes (de Mendoza 2014). In addition to the lipid structure of cell membranes, integral membrane proteins affect the temperature tolerance of an organism (Thompkins et al 2008). Therefore, while the lipid composition of the membrane is crucial for its function, integral membrane proteins may also play a significant role, particularly with respect to the temperature limit of an organism's growth range.…”
Section: Thermosipho Japonicus (Ab024932)mentioning
confidence: 99%